Crossroad between Inflammation, Iron and Lipids in Atherogenesis - Marques, Liliana (2013)
Atherosclerosis (ATH) is recognized as a chronic inflammatory condition and it is the leading cause of cardiovascular disease. The process of atherogenesis is characterized by the accumulation and oxidation of LDL (oxLDL) in the vessel wall and subsequent infiltration and activation of immune cells, particularly monocytes in an earlier stage and, later on, lymphocytes. The infiltrated monocytes differentiate into macrophages which then could differentiate into foam cells as a consequence of oxLDL uptake [1]. The recruitment of immune cells to the site of ATH lesion contributes to a local pro-inflammatory state that will promote the development of the atheroma plaque and progression of the disease. However, the exact mechanisms involved in this process are not fully understood. One hypothesis is the contribution of oxidative stress mediated by metals such as iron [2]. Previous authors have shown high iron content in foam cells and also accumulation of hemoglobin and ferritin in the areas rich in foam cells [3]. Herein, we investigate a possible mechanism for cellular iron accumulation by testing the effect of pro-inflammatory as well as pro-atherogenic stimuli in the expression of proteins involved in iron efflux in macrophages.